Effect Of Prenatal Yoga On Third Trimester Pregnant Women’s to Reduce Anxiety - Dian Taviyanda; Selvia David Richard; Agnes Martha Filipus (LPPM STIKes Muhammadiyah Ciamis, 2020)
Objective : Forms of anxiety experienced by third trimester mothers include doubts about being able to give birth normally, smooth delivery, fear of not being able to withstand the pain experienced during childbirth, condition of the baby being born, delivery not as desired, condition of the mother after giving birth, indirectly met her baby after giving birth, and received less attention from those around her. Prenatal Yoga is a non-pharmacological therapy in reducing anxiety in pregnant women. The purpose of the study was to determine the effectiveness of prenatal yoga in reducing anxiety in third trimester pregnant women in Bangsal RW 2 Kediri. Method : The method used in this study was experimental. The study population was third trimester pregnant women. The number of samples in the study was 35 respondents. This research uses purposive sampling. The variables used were prenatal yoga and anxiety. Researchers used a measuring instrument in the form of an Anxiety Scale for Pregnant (ASP) questionnaire. Result : The results of the research on anxiety in third trimester pregnant women before being given heavy prenatal yoga were 25 respondents (71.4%), after being given prenatal yoga anxiety in third trimester mild pregnant women were 32 respondents (91.4%) with Wilcoxon test results p = 0.000. Conclusion : The conclusion of this study is that prenatal yoga is very effective in reducing anxiety in third trimester pregnant women.